Implementasi Nilai-Nilai Kearifan Lokal Minang Kabau “Sumbang Duo Baleh” sebagai Upaya Pengembangan Kepribadian Mahasiswa Calon Guru - Sudirman Sudirman; Yuhasnil Yuhasnil; Larisman Larisman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study is how the implementation of the values of local wisdom sumbang dua baleh is realized in forming the personality of prospective teachers who become role models for students and support their professional careers as teachers in the future. This research method uses a qualitative research type with a phenomenological approach. The results of the study show that the values of local wisdom Sumbang duo baleh can be values that we can take as a source of values in building and forming the character and personality competencies of STKIP Yayasan Abdi Pendidikan students as prospective teachers for the better. The conclusion of this study is that by implementing the values of local wisdom Minang Kabau, it is hoped that the personality of teachers will be formed as role models for students and support their professional careers as teachers. Keywords: Local Wisdom Values, Minang Kabau, Personality, Prospective Teachers, Sumbang Duo Baleh.